The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.7763/ijcee.2013.v5.690
|View full text |Cite
|
Sign up to set email alerts
|

Power Quality Analysis of Photovoltaic Generation Integrated in User-Side Grid

Abstract: Abstract-This paper analyzes impacts of grid-connected photovoltaic power plant on the harmonic current in the power quality aspect of distribution network, Summaries the requirement of harmonic current injecting in grid caused by photovoltaic power plant which connected in user side. Based on the DIgSILENT PowerFactory simulation platform, this paper simulates harmonic current injecting into grid in one case of grid-connected photovoltaic generation and then analyzes it by build models of photovoltaic generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Similar THD influence and distorted current result for a PV power plant can be found in [8][9][10][21][22][23][24][25][26][27]. Generally, it can be concluded that the overall PV contribution to the total system THD is less than 2% and never exceeds the value of 4 % on the PCC.…”
Section: Distributed Generation Harmonic Influencesupporting
confidence: 71%
“…Similar THD influence and distorted current result for a PV power plant can be found in [8][9][10][21][22][23][24][25][26][27]. Generally, it can be concluded that the overall PV contribution to the total system THD is less than 2% and never exceeds the value of 4 % on the PCC.…”
Section: Distributed Generation Harmonic Influencesupporting
confidence: 71%
“…The power system network consists of many characteristics as table 1. The Plaukdeang Simulation System -the power flow analysis method [6,7] -that without connection of PV power plant is run to be base case simulation system by varying characteristic of load as peak load, part load and light load. The system is shown in figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…Existing literature has analyzed the impacts of rooftop and utility-scale PV fleets on representative distribution grids using load flow simulations. Broadly studied parameters include changes in feeder voltage profiles, line losses, power quality, and protection coordination with increasing solar generation [5][6][7]. However, there remains a lack of clarity among distribution utilities on permissible penetration thresholds before upgrades like battery storage and reactive power support become necessary.…”
Section: Introductionmentioning
confidence: 99%